The mobile classroom: Alternative educational space for vulnerable early childhood groups - Álvarez-Barrantes, José Alberto (Universidad ORT Uruguay, 2021)
In the present essay, architectural and educational arguments are used as a specific demand before the urgent requirement of early childhood educational populations in vulnerable Peruvian areas. These arguments reinforce the urgent need for the implementation of an architectural product (the mobile classroom) that would provide a livability solution for children of the initial level in areas of extreme poverty where neither the State has coverage nor the private sector is interested. It begins with the background and a brief theoretical framework that allows the description of the problem; Finally, this problem is attempted to be solved through a hypothesis that is embodied in an architectural design proposal called “mobile classroom”. Design that follows the recommendations of the Peruvian regulations and that gathers the experiences of other places that have had the same need, but adequate to the reality of a town called La Shilla, on the outskirts of the city of Cajamarca-Peru.